Nome Circle showing the Oregon Building, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of photograph: Looking southwest across Nome Circle, toward the Cascades. Caption on image: x2054 PH Coll 727.154 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number